Brief review of one dimensional neighbor balanced designs since 1967 - Rashid Ahmed; Munir Akhtar; Fariha Yasmin (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2011)
Rees (1967) introduced neighbor designs in serology. Since then it is well investigated field. Neighbor balanced designs are more useful to remove the neighbor effects in experiments where the performance of a treatment is affected by the treatments applied to its neighboring plots. Neighbor designs ensure that treatment comparisons will be less affected by neighbor effects as possible. This paper will provide an overview of the most important developments in this field.
Keywords: 330; Neighbor designs; Generalized neighbor designs; Second order neighbor designs; All order neighbor balanced designs